The Acculturation of Islam and Customary Law: an Experience of Minangkabau, Indonesia - Erwati Aziz (P3M STAIN Kudus, 2020)
Islam as an unperceived religion from an essentialist perpective, beause it is transhistorical. The reality shows that the expression of Islam in one particular geographical context is a result of the interplays between Islamic teachings and local culture. This is a qualitative studyon Minangkabau customs and culture, with data collected by reviewing documents, both in the form of books, and articles. In addition, interviews were conducted with a number of Minang figures, and added to the Minang residents experiences. The results showed that the Minangkabau customs and culture had acculturated with Islam since it was introduced to the Minang region around the 8th century AD. Before its introduction, there were customs and cultures based on their habits. This acculturation occurs peacefully, therefore, the decisions of the traditional leaders do not cause turmoil and resistance from adat stakeholders in the region. Acculturation of Minang customs and culture with Islam takes the form of synthetism, while adat adapts to its teachings. When Islam with Minang customs and culture blend into one, changes occur in three forms. Firstly, when the custom is not in accordance with the Islamic teachings, it is adjusted, as illustrated in the Minang customary philosophy which reads, “Adat basandi alua jo patuik, alua jo patuik basandi bana, bana badiri sandirinyo” changed into “Adat basandi Syara’, Syara’ basandi Kitabullah”. Secondly, both customs and culture, which are in line with Islam remain preserved, such as the principle of deliberation (musyawarah) and consensus (mufakat). Thirdly, it led to the promulgation of Islam in a new culture that has not existed before, such as the Khatam Al-Qur’an ceremony for children.